The different types of tourists and their motives when visiting Alaska during the Iditarod. - Becker, Paulien (UiT The Arctic University of Norway, 2014)
This research investigates the different types of tourists and their motives while visiting Alaska during the Iditarod. According to Getz (2008), sports event tourism has increased over recent years and a clear link between major events, attracting tourists and generating a positive destination image can be seen. In this perspective, the Iditarod is a mix of sporting events and touristic activities that capture the arctic wilderness. The longest and one of the most popular sled dog races in the world, known as the Iditarod is held in Alaska. The first race was completed in 1973. From 1976, the Iditarod gained national and international credibility by calling the race; “The Last Great Race on Earth.” Now, national and international tourists are visiting Alaska in the wintertime to see the Iditarod. I have been following part of the Iditarod 2014 during my half-year stay in Alaska to conduct this research. The research question is formulated; “Who are the tourists visiting Alaska during the Iditarod, and what are their motives?” Understanding the tourists and their motivations is important to understand travellers behaviours, predict future travel patterns and it should help tourism industries to develop effective marketing programs to attract the travellers. (Jang & Wu, 2006) For this master thesis, mixed methods are used to conduct research. Three in-depth interviews are conducted with different tour operators based in Anchorage and Nome. The sample of tour operators is founded by two main criteria. The first is that tour operators are based in Anchorage and the second is that they are offering tours during the Iditarod. The in-depth interviews give the researcher information about the best locations for conducting the quantitative research. The locations for the quantitative research were the Mushers Drawing Banquet Anchorage, Day before Iditarod 2014 Race Start, Iditarod 2014 Race start, Iditarod 2014 Race Re-Start and the finish in Nome. After conducting a sample of 56 respondents spread over these ...